DRUG RESIDUE AVOIDANCE - Toillion, Alyssa (My University, 2017)
Antibiotics are used in food-producing animals to treat, prevent, and control diseases caused by harmful bacteria. Administration of antibiotics, anthelmintics, pesticides, parasiticides, and other therapeutic chemicals to food-producing animals can result in a residue. A residue is defined by the Food and Drug Administration (FDA) Center for Veterinary Medicine (CVM) as any compound or metabolite of a compound that is present in edible tissues from food animals because of the use of a compound in or on animals. Residues can be from the compound itself, its metabolites, or any other substances formed in or on food as a result of the compound's use. Any animal that receives any therapy that can result in residues cannot, by law, be sent to slaughter until the drug has been reduced to a specified level and deemed safe for human consumption. Drug concentrations above this level are illegal and known as violative residues. It is the responsibility of the producer to ensure the health, safety, and well-being of their animals while remaining in compliance with state and federal laws. Following labels and abiding by withdrawal times are crucial parts in protecting the food supply chain. Diseases can have a devastating impact on animal welfare and production. Consumers have expressed concern regarding the health impact of drug residues in their food. These concerns include: toxicity, allergic or hypersensitivity reactions, carcinogenic, mutagenic or teratogenic effects, the potential for the development and transfer of antibiotic resistant bacteria, and consumer preference of “antibiotic free” products. To avoid these concerns, all drugs should be used according to label directions and in a judicious manner. Drug residue avoidance begins by working with a veterinarian to put into place best management practices or “BMPs” and standard operating procedures or “SOPs” for a farm or operation. Following the formation of these BMPs and SOPs, all employees and stakeholders must be regularly trained and adherence to the BMPs and SOPs must be verified. Reading and following product-label directions, maintaining good records, and adopting a quality assurance program, all contribute to maintaining the safest food supply chain in the world. The Kansas Department of Agriculture received a grant through the FDA with the goal to prevent violative drug residues in animal-derived foods produced in Kansas through educational training and outreach to livestock producers. This was accomplished through three communication strategies: brochures, PowerPoint slide sets, and online training modules. Specific educational materials were created for five different animal production segments: beef cattle, dairy cattle, swine, poultry, and small ruminants. Upon completion, these materials will be made available on the Kansas Department of Agriculture’s website.
Keywords: drug residue; public health; antibiotics; food safety; withdrawal time; toxicology